Differential impact of severe familial hypercholesterolemia on regional skeletal muscle and organ blood flows during exercise: Effects of PDE5 inhibition. (26th March 2019) - Aragonez, Christian G.; de Beer, Vincent J.; Tharp, Darla L.; Bowles, Douglas K.; Laughlin, M. Harold; Merkus, Daphne; Duncker, Dirk J.; Bender, Shawn B.
Abstract: Objective: Swine with familial hypercholesterolemia (FH) exhibit attenuated exercise‐induced systemic vasodilation that is restored by phosphodiesterase 5 (PDE5) inhibition. Whether the impacts of FH and PDE5 inhibition to impair and restore exercise‐induced vasodilation, respectively, results from tissue‐specific or generalized effects remains unclear. Thus, we hypothesized that FH induces generalized impairment of skeletal muscle vasodilation that would be alleviated by PDE5 inhibition. Methods: Systemic vascular responses to exercise were assessed in chronically instrumented normal and FH swine before and after PDE5 inhibition with EMD360527. Skeletal muscle and organ blood flows and conductances were determined via the microsphere technique. Results: As previously reported, vs normal swine, FH swine have pronounced elevation of total cholesterol and impaired exercise‐induced vasodilation that is restored by PDE5 inhibition. Blood flows to several, not all, skeletal muscle vascular beds were severely impaired by FH associated with reduced blood flow to many visceral organs. PDE5 inhibition differentially impacted skeletal muscle and organ blood flows in normal and FH swine. Conclusions: These data indicate that FH induces regional, not generalized, vasomotor dysfunction and that FH and normal swine exhibit unique tissue blood flow responses to PDE5 inhibition thereby adding to accumulating evidence of vascular bed‐specific dysfunction in co‐morbid conditions.